Redefining The Roles of Islamic Organizations in the Reformasi Era - Burhanudin, Jajat (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2010)
Center for the Study of Islam and Society (PPIM) of State University Syarif Hidayatullah, Jakarta, in cooperation with Center for the Study of Society and Culture (PMB) of Indonesian’s Science Foundation (LIPI), and Research Institute for Languages and Cultures of Asia and Africa (ILCAA) of Tokyo University of Foreign Studies (TUFS), held a conference on “Redefining the Roles of Islamic Organizations in the Reformasi Era. ”The conference was divided into two sessions. In the first session we have Prof. Dr. Bahtiar Effendy, Dr. Hendro Prasetyo, and Drs. Anas Ahmadi, MA. In the second session we have Dr. Endang Turmudi from Nahdhatul Ulama (NU) and Dr. Abdul Mu’ti from Muhammadiyah.The seminar was designed to evaluate and discuss the roles of socio-religious organizations in Indonesia. The current understanding on the roles of socio religious organizations was being challenged and questioned. The seminar discussed the relationship between the state and the roles of these religious organizations during the Reformasi Era. These were among the important issues because transformation of ideas and movements have occurred within Islamic organizations in Indonesia.Since the beginning of the twentieth century, socio-religious organizations have played important roles in Indonesia’s nation building. Muhammadiyah, NU, and Persis are among the organizations which have contributed significantly to the development of Islam in Indonesia. They have been the driving forces for community development such as in education, socio-political, economy, and health. Most of the madrasah and pesantren across Indonesia were founded by these organizations.DOI: 10.15408/sdi.v17i2.466